PEMBIAYAAN SINDIKASI SEBAGAI PENINGKATAN PORTOFOLIO PEMBIAYAAN PERBANKAN SYARIAH - Rahmayati Rahmayati (Institut Agama Islam Negeri Padngsidimpuan, 2019)
AbstractThe purpose of this study is to examine that syndicated financing has a great opportunity in improving the financing portfolio at Bank Aceh Syariah. This research method is designed as a descriptive study, which aims to describe the nature or characteristics of a symptom, events, events that occur at this time. The data of this study is an explanatory survey sourced from data in the form of financial data from PT. Bank Aceh Syariah. This research was conducted at PT. Bank Aceh Syariah by taking secondary data that is based on data from the syndicated financing portfolio at PT. Bank Aceh Syariah. Data analysis methods are based on supporting references, financial reports, and other sources. Based on this study the authors conclude a number of things, first, that the syndicated financing opportunity is large. Second, the higher the syndicated financing, the higher the financing portfolio at PT Bank Aceh Syariah. Third, syndicated financing has a more acceptable risk because the project being financed is a strategic project and the risk is shared between fellow syndicated participants. Thus the study of syndicated financing will be carried out as an increase in the financing portfolio at Bank Aceh Syariah.AbstrakTujuan dari penelitian ini adalah untuk mengkaji peluang pembiayaan sindikasi dalam peningkatan portofolio pembiayaan di Bank Aceh Syariah. Penelitian ini merupakan penelitian deskriptif, berbentuk explanatory survey yang bersumber pada data berupa data-data keuangan dari PT. Bank Aceh Syariah. Penelitian ini dilakukan di PT. Bank Aceh Syariah dengan mengambil data sekunder yaitu berdasarkan data portofolio pembiayaan sindikasi yang terdapat di PT. Bank Aceh Syariah. Metode analisis data yaitu berdasarkan referensi yang mendukung, laporan keuangan, dan sumber-sumber lainnya. Berdasarkan penelitian ini penulis menyimpulkan beberapa hal yaitu pertama, bahwa peluang pembiayaan sindikasi besar. Kedua, Semakin tinggi pembiayaan sindikasi maka akan semakin meningkat portofolio pembiayaan di PT Bank Aceh Syariah. Ketiga, Pembiayaan sindikasi memiliki resiko yang lebih akseptable karena proyek yang dibiayai adalah proyek strategis dan risiko dibagi antara sesama peserta sindikasi. Dengan demikian akan dilakukan pengkajian terhadap pembiayaan sindikasi ini sebagai peningkatan portofolio pembiayaan di Bank Aceh syariah.